THE PROBLEM OF DISCIPLINARY FORMATION IN POLITICAL SCIENCE AS AN INDICATOR OF ITS INTERDISCIPLINARY AND INTEGRATIVE NATURE - Rubanov, Victor (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The relevance of profile research into the problems of the constitution and real functioning of political science as a scientific discipline is established. Based on the latest theoretical and fundamental research of scientists and real empirical facts, as it appears, an attempt is being made to conceptually explain the interdisciplinary and integrative nature of flight biology as a scientific dissertation. chicks. The renowned author, for the first time in scientific literature, reveals the peculiarities of the Kharkiv school of political analysis, its role in the theoretical-fundamental and institutional development of political science itself disciplinary and integrative scientific discipline. In conclusion, it reveals not only the significance of the world’s first political science professors Tikhon Stepanov and Andriy Kachenovsky in these processes, but also the role of the first specialized professional practical about applied institutions of the university in constitutional political science as an interdisciplinary and integrative scientific discipline. In realizing this goal, the author points out that this very aspect of political science is embedded in Aristotle’s well-known characterization as «the queen of all sciences». Moreover, according to the author’s opinion, in this very fact, there is not only a theoretical characteristic of the nature of political science, but also a practical - applied significance in the initial process of training future political scientists ів – the ability to integrate, to bring together disparate layers of knowledge, such as were accumulated by students for the hardships of their studies in science. First of all, this is due to the fact that a certain proportion of them reflect on the current problems of the domestic and international political present, without even mentioning the basic achievements of political scientists of Ukraine and, in particular, the Kharkiv School of Political Science. Therefore, the proposed article may be useful for current and future political scientists.